METHODOLOGY FOR DESIGNING THE PROCESS OF DEVELOPING SPEECH COMPETENCE IN PRIMARY SCHOOL STUDENTS (International journal of artificial intelligence, 2025)
this article explores the model of designing this process, highlighting the problems and opportunities inherent in the development of effective verbal communication skills during the formative years of primary education.